2013
DOI: 10.1080/15222055.2013.786006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aquaflor (50% Florfenicol)–Medicated Feed to Control Mortality Associated with Flavobacterium columnare Infection in Florida Largemouth Bass and Bluegill

Abstract: Aquaflor (florfenicol, 50% with/without) is a potent, broad‐spectrum, antibacterial agent with bacteriostatic properties that are active against a variety of Gram‐positive and Gram‐negative bacteria. This product is approved by the U. S. Food and Drug Administration for use on several fish species to control mortality associated with a variety of diseases, including columnaris (causative agent, Flavobacterium columnare). Two independent experimental trials were separately conducted to evaluate the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Several antimicrobials, including three oral antibiotics, are approved by the U.S. Food and Drug Administration (FDA) for use to control mortality in captive-reared fish associated with a variety of diseases (Matthews et al 2013). However, their use is restricted to specific disease indications and treatment regimens (FDA 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several antimicrobials, including three oral antibiotics, are approved by the U.S. Food and Drug Administration (FDA) for use to control mortality in captive-reared fish associated with a variety of diseases (Matthews et al 2013). However, their use is restricted to specific disease indications and treatment regimens (FDA 2012).…”
mentioning
confidence: 99%
“…Because of its high potency and because it is not used in human medicine, florfenicol has become an important veterinary therapeutic drug, especially when administered in feed. Florfenicol can control mortality caused by furunculosis in Atlantic Salmon Salmo salar (Nordmo et al 1994;Samuelsen et al 1998), pseudotuberculosis in Yellowtail (buri) Seriola quinqueradiate (Yasunaga and Yasumoto 1988), columnaris in Largemouth Bass Micropterus salmoides, and Bluegill Lepomis macrochirus (Matthews et al 2013), and streptococcal disease 517 518 BOWKER ET AL. in sunshine bass (female White Bass Morone chrysops × male Striped Bass M. saxatilis) (Darwish 2007;Bowker et al 2010) and Nile Tilapia Oreochromis niloticus (Gaunt et al 2010). In addition, florfenicol caused no mortalities, changes in fish growth, or clinical changes in Channel Catfish Ictalurus punctatus (Gaikowski et al 2003) when fed for 20 d at doses up to 34.9 mg florfenicol·kg fish −1 ·d −1 or in sunshine bass (Straus et al 2012) when fed for 20 d at doses up to 75 mg florfenicol·kg fish −1 ·d −1 .…”
mentioning
confidence: 99%
“…Florfenicol has also been effective against other fish pathogens infecting cultured freshwater including Aeromonas salmonicida subsp . salmonicida, the cause of furunculosis in salmonids (Inglis, Richards, Varma, Sutherland, & Brokken, ; Samuelsen, Hjeltnes, & Glette, ); F. columnare , the aetiology of columnaris disease (Matthews et al, ); Vibrio anguillarum , a cause of vibriosis in cod (Samuelsen & Bergh, ) and Edwardsiella ictaluri , the cause of enteric septicaemia in catfish (Gaunt et al, ). Previous in vitro study suggested the potential of ERY for treating F. psychrophilum infections (Hesami et al, ).…”
Section: Discussionmentioning
confidence: 99%